Piotr Idczak, Ida Musiałkowska, Financial engineering in sustaible funding of urban development in the EU. Reflections on the JESSICA Initiative, De Gruyter, Berlin/Boston, 2022, ss. 243. - Małuszyńska, Ewa (Rocznik Integracji Europejskiej, 2023)
Oceny i omówienia: Piotr Idczak, Ida Musiałkowska, Financial engineering in sustaible funding of urban development in the EU. Reflections on the JESSICA Initiative, De Gruyter, Berlin/Boston, 2022, ss. 243.(Ewa Małuszyńska)